Pengaruh Pemberian Zat Pengatur Tumbuh Giberelin Terhadap Pertumbuhan dan ProduksiTanaman Melon (Cucumis melo L.) - Marendi, Rezhy Anca; Murniati, Murniati; Nurbaiti, Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to determine the effect of the administration of gibberellins ZPT and obtain the best ZPT concentration on the growth and production of melon plants. The study was conducted in the Experimental Garden of the Faculty of Agriculture, University of Riau, Tampan District, Pekanbaru. The height of the study site is 10 m above sea level. The study was conducted for three months, starting from March to May 2018. The research was conducted experimentally using a Randomized Block Design (RBD) consisting of five treatments. Each treatment was repeated 4 times, so that 20 experimental units were obtained. The treatment given consisted of several concentrations of gibberellins (0, 20, 40, 60 and 80) ppm. The parameters observed were plant length, number of leaves, fruit length, fruit diameter, fruit weight and fruit thickness. The data obtained were analyzed statistically using variance analysis. The results of variance obtained were then further tested using Duncan's multiple range test at a level of 5%. administration of different concentrations of gibberellins ZPT, showed the same results in parameters of plant length, number of leaves, fruit length, fruit diameter and fruit weight.Â Â Keyword : Gibberellins, ZPT, Melon Plants.